Analisis Tahap Religius Mahasiswi Melaksanakan Ajaran Agama: Studi Pada Mahasiswa Asrama di Perguruan Tinggi - Guslianto, Guslianto; Fitri, Rika; Asril, Zainal; Hasnah, Hasnah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2023)
The level of worship is an achievement that needs to be improved by a servant to be more active in performing worship. This research analyzes how female students obey religious teachings or worship in life. This research uses a qualitative method with a case study approach. Data sources were taken from sixteen informants through in-depth interviews who were selected using techniques of purposive sampling. All informants are active students from various departments at one of the universities in Indonesia. All interview results were then analyzed thematically using the Analysis Interactive Model Milles & Hubberman. The results of the analysis show that there are four levels of worship carried out by female students, namely prayer observance, fasting, reading the Quran, and almsgiving. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.